Gustavus Scott correspondence - Scott, Gustavus, 1753-1800.
ALS (1797 April 24) written by Scott to John Nicholson relating to politics and a letter (1800 January 7) from Scott and William Thornton to the Bank of Columbia regarding a financial matter.
Lawyer and delegate to the U.S. Continental Congress from Maryland.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Nicholson, John, -- 1757-1800 -- Correspondence; Thornton, William, -- 1759-1828 -- Correspondence; Bank of Columbia (Georgetown, Washington, D.C.); Banks and banking -- Washington (D.C.); United States -- Politics and government -- 1797-1801.; Delegates, U.S. Continental Congress -- Maryland; Lawyers